Louise Erdrich’s Future Home of the Living God: Uncertainty, Proleptic Mourning and Relationality in Native Dystopia - Martínez-Falquina, Silvia (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2019)
This article examines Louise Erdrich’s latest novel Future Home of the Living God (2017) in the light of the current conversation about the attacks on women’s reproductive rights and the devastating effects of climate change. Erdrich’s speculative novel describes an unspecified future where evolution has reversed itself and human reproduction is under threat, as a response to which a Puritan authoritarian government takes control of women of childbearing age to try to sustain procreation. The article contends that, using the dystopian mode—and more specifically, a theorization of uncertainty as characteristic of the present situation of many people—Erdrich addresses persisting, historical unresolved grief, making current feminist and Native vindications visible. She also continues the challenging of the whitestream idea of progress and the subversion of stereotypes that characterize her oeuvre. Most significantly, the article reads the novel as representative of both Indigenous resurgence and the global transmodern paradigm insofar as it articulates a relational understanding of language and identity as our best hope for the future. The article concludes that Erdrich’s use of the future perfect tense is best interpreted as a ritual of proleptic mourning that connects this novel to Native American literary activism. Keywords: Louise Erdrich; Native dystopia; Native American resurgence; transmodernity; relationality; proleptic mourning